RFG: An Interactive Fiction Game to Stimulate Software Requirements Learning - Corrêa, Chessman K. F.; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
Software development begins with the elicitation of different types of requirements. Therefore, students must learn elicitation techniques and the types of requirements to carry out this activity. The teaching and learning process has been described as a challenge. Due to this, Game-Based Learning was created to use games to improve the engagement and learning of students. Different kinds of games have been proposed to improve the learning of requirements. In this paper, we describe a text-based interactive fiction game for learning software requirements.